Coherent Random-Modulated Continuous-Wave LiDAR Based on Phase-Coded Subcarrier Modulation - Zhongyang Xu (MDPI AG, 2021)
A coherent random-modulated continuous-wave (RMCW) LiDAR transmits a lightwave modulated by a pseudo-random binary sequence (PRBS). The lightwave backscattered from targets is received and used to reconstruct the PRBS. Then, the time-of-flight is extracted by correlating the reconstructed PRBS and the original PRBS. We propose a coherent RMCW LiDAR based on phase-coded subcarrier modulation, in which the impacts of internal reflection and optical Doppler frequency shift (DFS) are mitigated. A continuous lightwave is amplitude-modulated by an RF signal which is phase-coded with a PRBS. Coherent detection is used in the receiver. A beat signal that consisted of a low-frequency signal and a high-frequency signal is obtained by a single balanced photodetector (BPD). The optical DFS can be directly extracted from the low-frequency signal. It is used to compensate for the frequency offset of PRBS, which is extracted from the high-frequency signal. In addition, the background noise caused by internal reflection is suppressed by averaging over successive measurement spots. In this paper, the performance of a coherent RMCW LiDAR is firstly analyzed by numeric simulations and demonstration experiments. Then, line-scanning measurements for moving targets are implemented to demonstrate the 3D imaging capability of the proposed coherent RMCW LiDAR.